The protective effects of beta-mangostin against sodium iodate-induced retinal ROS-mediated apoptosis through MEK/ERK and p53 signaling pathways - Chang, Yuan-Yen; Wang, Meilin; Yeh, Jui-Hsuan; Tsou, Shang-Chun; Chen, Tzu-Chun; Hsu, Min-Yen; Lee, Yi-Ju; Wang, Inga; Lin, Hui-Wen (Food & function, 2023)
Previous studies have indicated that NaIO 3 induces intracellular reactive oxygen species (ROS) production and has been used as a model for age-related macular degeneration (AMD) due to the selective retinal pigment epithelium (RPE) cell damage it induces. Beta-mangostin (BM) is a xanthone-type natural compound isolated from Cratoxylum arborescens . The influence of BM on NaIO 3 -induced oxidative stress damage in ARPE-19 cells has not yet been elucidated. In this study, we investigated how BM protects ARPE-19 cells from NaIO 3 -induced ROS-mediated apoptosis. Our results revealed that BM notably improved cell viability and prevented ARPE-19 cell mitochondrial dysfunction mediated-apoptosis induced by NaIO 3 ; it was mediated by significantly reduced NaIO 3 -upregulated ROS, cellular H 2 O 2 production and improved downregulated glutathione and catalase activities. Furthermore, we found that BM could suppress the expression of Bax, cleaved PARP, and cleaved caspase-3 by decreasing phosphorylation of MEK/ERK and p53 expression in NaIO 3 -induced ARPE-19 cells. At the same time, we also used MEK inhibitors (PD98059) to confirm the above phenomenon. Moreover, our animal experiments revealed that BM prevented NaIO 3 from causing retinal deformation; it led to thicker outer and inner nuclear layers and downregulated cleaved caspase-3 expression compared to the group receiving NaIO 3 only. Collectively, these results suggest that BM can protect the RPE and retina from NaIO 3 -induced apoptosis through ROS-mediated mitochondrial dysfunction involving the MEK/ERK and p53 signaling pathways. Previous studies have indicated that NaIO 3 induces intracellular reactive oxygen species (ROS) production and has been used as a model for age-related macular degeneration (AMD) due to the selective retinal pigment epithelium (RPE) cell damage it induces.